The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/jctb.7072
|View full text |Cite
|
Sign up to set email alerts
|

The role of Acidithiobacillus ferrooxidans in Fe(II) oxidation of pyrite in bioleaching processes

Abstract: BACKGROUND Microbial leaching is an emerging ore extraction technology, especially for low‐grade ores. In sulfide and oxide ore bioleaching systems, Acidithiobacillus ferrooxidans is becoming a widely applied microorganism for mineral processing. Many studies are currently focusing on the vital role of A. ferrooxidans in facilitating the efficiencies of sulfur and iron species transformation for sulfide ore bioleaching. Existing research usually investigates the composite action of A. ferrooxidans and Fe(III) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Thus, the effective management of pulp density is a critical aspect of maximizing the process efficiency. Additionally, in the study "The Role of Acidithiobacillus ferrooxidans in the Oxidation of Fe(II) Pyrite in Bioleaching Processes" by [27] Kang, Jin-xing et al, it was found that Acidithiobacillus ferrooxidans significantly accelerate the oxidation of Fe(II) in pyrite, thereby enhancing the efficiency of the biological leaching of this sulfide ore.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effective management of pulp density is a critical aspect of maximizing the process efficiency. Additionally, in the study "The Role of Acidithiobacillus ferrooxidans in the Oxidation of Fe(II) Pyrite in Bioleaching Processes" by [27] Kang, Jin-xing et al, it was found that Acidithiobacillus ferrooxidans significantly accelerate the oxidation of Fe(II) in pyrite, thereby enhancing the efficiency of the biological leaching of this sulfide ore.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, to the best of our knowledge, the potential application of microorganisms for RFB enhancement is barely to be investigated; only a few studies existed up to now. 23 , 24 The bacteria involved in ferrous oxidation/reduction processes are widely distributed in various natural and artificial ecosystems, which cause various environmental problems such as acid mine wastewater emission 25 , 26 and iron structure corrosion. 27 , 28 Certain iron reduction bacteria such as Geobacter have been widely employed in the remediation of soil and groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, bioleaching provides more surface area and roughness which in turn contributes toward electrochemical characteristics. 21,22 Acidithiobacillus ferrooxidans is a wellknown bacterium for the oxidation of ferrous ions. However, adding other metallic atoms (Cu, Co, Mn, Mo, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, controlled removal of iron can be achieved only through bacterial treatment, which is otherwise known as bioleaching, an ecofriendly method commonly used for mobilizing metals from waste, metal extraction, etc. In addition, bioleaching provides more surface area and roughness which in turn contributes toward electrochemical characteristics. , Acidithiobacillus ferrooxidans is a well-known bacterium for the oxidation of ferrous ions. However, adding other metallic atoms (Cu, Co, Mn, Mo, etc.)…”
Section: Introductionmentioning
confidence: 99%